ANALISIS KERAGAAN FENOTIPE F1 HASIL PERSILANGAN JARAK PAGAR (Jatropha Curcas L.) SEBAGAI SUMBER BELAJAR GENETIKA PEWARISAN SIFAT - Hindun, Iin (Universitas Sebelas Maret, 2014)
Abstract - Physic nut (Jatropha curcas L.) is a versatile plant and all parts of the body have the potential to be exploited. Government has set as a source of biofuels (BBN) in supporting the diversification of sources of alternative energy using the Physic nut. Utilization target is 5 % of Indonesia's energy mix by 2025. Seethes need to be supported in the future high yielding improved varieties. Problems faced are no varieties or clones produced Physic nut. Hybridization is one method to obtain high yielding varieties and has been done by breeders Physic nut. This study was conducted to look at a number of phenotypic variability F1 crosses of Physic nut in support of the data base of the hybrid varieties. The parameters observed were plant height, number of branches, number of leaves indentations and 100 seed weight. The results showed that the variability of phenotypes F1 hybridization of Physic nut plants vary in height, number of branches, 100 seed weight and nearly uniform in curvature amount of leaves. 4 hybridization each accession of parental: SP8 x SP16, F1 coded 5; SP8 x SP38, F1 coded 6; HS 49 x SP33, F1 coded 7; SP38 x SM35, F1 coded 18, the results showed there are differences and parent and offspring phenotype equations F1. F1 seed weight on yield was higher than the parent. This process and result can be used as a learning resource for studying the inheritance of the parent to the offspring at genetic learning in secondary schools.Â Key words : Physic nut, hybridization, phenotypes, learning resources